2022
DOI: 10.3390/nu14194217
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Supplementation for the Treatment of COVID-19: A Systematic Review and Meta-Analysis

Abstract: Since the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe respiratory syndrome coronavirus 2 (SARS-CoV-2), millions of people have died, and the medical system has faced significant difficulties. Our purpose was to perform a meta-analysis to estimate the effect of vitamin C on in-hospital mortality and the ICU or hospital length of stay for patients diagnosed with COVID-19. We conducted a systematic review with meta-analysis in the following databases: PubMed, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…Moreover, a systematic review and meta-analysis [ 47 ] demonstrated that antioxidants, especially Zn, and Se, vitamins C and D, improve COVID-19 clinical outcomes and reduce the severity. Another systematic review and meta-analysis [ 48 ] revealed that vitamin C supplementation reduces hospital mortality in COVID-19 patients, but ICU LOS and hospital LOS were longer in the patients who were treated with vitamin C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a systematic review and meta-analysis [ 47 ] demonstrated that antioxidants, especially Zn, and Se, vitamins C and D, improve COVID-19 clinical outcomes and reduce the severity. Another systematic review and meta-analysis [ 48 ] revealed that vitamin C supplementation reduces hospital mortality in COVID-19 patients, but ICU LOS and hospital LOS were longer in the patients who were treated with vitamin C.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a systematic review and meta-analysis [47] demonstrated that antioxidants, especially Zn, and Se, vitamins C and D, improve COVID-19 clinical outcomes and reduce the severity. Another systematic review and meta-analysis [48] revealed that vitamin C supplementation reduces hospital mortality in COVID-19 patients, but ICU LOS and hospital LOS were longer in the patients who were treated with vitamin C. This observed inconsistency among included studies may be due to the following causes: (a) antioxidants were used as the primary treatment in certain investigations, while in others, they served as a co-adjuvant to formal experimental therapy. (b) The hospital setting (inpatient vs. outpatient) and ethnicity varied between studies.…”
Section: Discussionmentioning
confidence: 99%
“…There has recently been emerging evidence for the use of vitamin C as a treatment for sepsis [ 20 ]. Similarly, high-dose intravenous vitamin C (HDIVC) treatment has been reported to be effective in decreasing days of hospitalization, ICU stay and mortality in patients with COVID-19 [ 16 , 17 , 18 , 36 ]. Bypassing the limitations of vitamin C uptake through a sodium-dependent vitamin C transporter (SVCT1), HDVIC can achieve 70-fold higher plasma concentrations of vitamin C compared to oral administration [ 180 ].…”
Section: Vitamin C Therapy In Covid-19mentioning
confidence: 99%
“…It is likely that ascorbate therapy alone, or nitrate (or nitrite) therapy alone, may be insufficient to drive the reductive mechanism. A combination of these factors, as well as the appropriate mode of delivery (intravenous administration or oral administration), could be required to maximize the effects, which is a possible reason why HDIVC treatment in the ICU is sometimes ineffective or has effects opposite to our expectations [ 18 ].…”
Section: Vitamin C Therapy In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation